Incretins-Based Therapies and Their Cardiovascular Effects: New Game-Changers for the Management of Patients with Diabetes and Cardiovascular Disease - Federico Bernardini; Annunziata Nusca; Federica Coletti; Ylenia La Porta; Mariagrazia Piscione; Francesca Vespasiano; Fabio Mangiacapra; Elisabetta Ricottini; Rosetta Melfi; Ilaria Cavallari; Gian Paolo Ussia; Francesco Grigioni (MDPI AG, 2023)
Atherosclerosis is the leading cause of death worldwide, especially in patients with type 2 diabetes mellitus (T2D). GLP-1 receptor agonists and DPP-4 inhibitors were demonstrated to play a markedly protective role for the cardiovascular system beyond their glycemic control. Several cardiovascular outcome trials (CVOT) reported the association between using these agents and a significant reduction in cardiovascular events in patients with T2D and a high cardiovascular risk profile. Moreover, recent evidence highlights a favorable benefit/risk profile in myocardial infarction and percutaneous coronary revascularization settings. These clinical effects result from their actions on multiple molecular mechanisms involving the immune system, platelets, and endothelial and vascular smooth muscle cells. This comprehensive review specifically concentrates on these cellular and molecular processes mediating the cardiovascular effects of incretins-like molecules, aiming to improve clinicians' knowledge and stimulate a more extensive use of these drugs in clinical practice as helpful cardiovascular preventive strategies.